Suburban space, the novel and australian modernity. - ROONEY, BRIGID (Anthem studies in australian literature and culture, 2018)
'Suburban space, the novel and Australian modernity' investigates the interaction between suburbs and suburbia in a century-long series of Australian novels. It puts the often trenchantly anti-suburban rhetoric of Australian fiction in dialogue with its evocative and imaginative rendering of suburban place and time.